Anticancer and Antioxidant activity of Gold Nanoparticles Biosynthesized using Acinetobacter baumannii - Al-Abdeli, Intesar H.; Al-kalifawi, Esam J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In the current study, gold nanoparticles were made using Acinetobacter baumannii broth culture. UV-vis, FTIR, XRD, FESEM, AMF, and zeta potential measurements were also used to study the properties of the Ab-AuNPs. The average was 66 nm, ranging from 20 to 90 nm. The examination results proved that the Ab-AuNPs are semi-spherical and varied from 20 to 90 nm, with an average of 66 nm.    MTT assay on the breast cancer cell line MCF-7 confirmed the anticancer activity in vitro. Cancer cells showed an important cytotoxic activity of Ab-AuNPs. The breast. Cancer cell. Line.MCF-7 but ineffective against the normal.cell line.MCF-10. The IC50 values of Ab-AuNPs were at 11.45 μg ml-1. The results proved that Ab-AuNPs have DPPH scavenging activity, which increases with increasing concentration of Ab-AuNPs, where the concentrations (3.1, 6.25, 12.5, 25, and 50) mg/m gave DPPH scavenging activity with the following values 37.87%, 50.13%, 59.33%, 75.55%, and 85.13% respectively.   The present study concludes that gold nanoparticles synthesized using A. baumannii broth culture are easy to prepare, inexpensive, and non-toxic to normal cells. Meanwhile, they possess antioxidant and anticancer activity. So, it can be used as an alternative treatment.